Competition and Globalization of Business to Further Develop Creativity and Innovation for the Advancement of the Company ( Case Study at PT. Top Drink World) - Slamet Heri Winarno, Slamet Heri Winarno; Lela Elvira, Lela Elvira; Jeffry Latumahina, Jeffry Latumahina; Sabil Sabil, Sabil Sabil; RR Roosita Cindrakasih, RR Roosita Cindrakasih; Syah Putra, Arman (CV. Inara, 2022)
The background of this research is how to determine competition and globalization in terms of business to increase creativity and innovation. For the sake of the progress of a company. Therefore, in this study, we will discuss how competition and what innovations are needed by a company so that the company can advance and develop in the future, hard right now. The method used in this study is to use the literature review method and use the market analysis method so that it can be ascertained what is needed by the company to develop so that the weaknesses and strengths of a company can be known. The problem raised in this research is how to develop creativity and innovation from a product. For the sake of the company's progress in the current era of global competition, innovation is very necessary in order to help sales in this increasingly difficult market. The purpose of this research is how to determine the innovations that can be developed by a company in order to increase sales and can help the company grow bigger so that it can compete in national and international markets.